2014
DOI: 10.1128/jcm.01903-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of pncA and rpsA Gene Sequencing in Detection of Pyrazinamide Resistance in Mycobacterium tuberculosis Isolates from Southern China

Abstract: cWe sequenced pncA and rpsA genes plus flanking regions of 161 Mycobacterium tuberculosis isolates and found 10 new pncA and 3 novel rpsA mutations in pyrazinamide-resistant strains determined by the Bactec MGIT 960 system. The 3= end of rpsA might be added as the target of molecular detection of pyrazinamide susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
70
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 31 publications
11
70
1
Order By: Relevance
“…Reports mentioned a certain concentration of pncA mutations at amino acid residues 3 to 12, 46 to 62, 68 to 85, 94 to 103, and 132 to 142, which were areas near pyrazinamidase's active sites (Cys138, Asp8, and Lys96) or metal ion binding sites (Asp49, His51, His57, and His71) (21,22). We found that 71.23% of the mutations were located in the regions, which was a result similar to some reported previously (3,6,19,(23)(24)(25). Five novel mutations were identified in the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Reports mentioned a certain concentration of pncA mutations at amino acid residues 3 to 12, 46 to 62, 68 to 85, 94 to 103, and 132 to 142, which were areas near pyrazinamidase's active sites (Cys138, Asp8, and Lys96) or metal ion binding sites (Asp49, His51, His57, and His71) (21,22). We found that 71.23% of the mutations were located in the regions, which was a result similar to some reported previously (3,6,19,(23)(24)(25). Five novel mutations were identified in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…Previous publications suggested that phenotypic resistance to PZA had a strong correlation with mutations in the coding and promoter regions of pncA (18,19). Accordingly, we observed that 92 PZA-resistant isolates had 53 mutations in these regions.…”
Section: Discussionsupporting
confidence: 60%
“…Duplicates of the M. tuberculosis H37Rv reference strain were included in each run as inter-and intrareplication quality controls. A MIC of more than 500 mg/liter was defined as high-level resistance to PZA (4,12).…”
Section: Settingsmentioning
confidence: 99%
“…Mutations or variations in pncA leading to the loss of PZase activity is the major mechanism leading to PZA resistance (3). However, while high numbers of PZA-resistant cases can be related to inactivation of the PZase, the genetic variants, including single nucleotide polymorphisms (SNPs) and small deletions, are highly diverse and scattered over the full length of the 561-bp pncA gene (4,5). This complicates the development of molecular tests, as no "hot spot region" comprising the majority of mutations is observed in the pncA gene.…”
mentioning
confidence: 99%
“…The low sensitivity and specificity of HRM in this study could be due to the use of three sets of primers as compared to five or seven as used in previous studies [40] [41].…”
Section: Discussionmentioning
confidence: 73%